Financial Performance on Improving The Quality of Human Resources in Higher Education - Syarifuddin, Syarifuddin (JURNAL AL-TANZIM, 2022)
This study aims to analyze and understand financial performance in improving the quality of human resources in high school lecturers. This study uses a qualitative data collection case study type. The data collection technique is done through interviews, observation, and documentation. Meanwhile, the data analysis was carried out circularly, starting with data collection and reduction and concluding. The results showed that financial performance to improve the quality of human resources through the balanced scorecard approach at the University of Muhammadiyah Berau was effective. This is because the university's Balanced scorecard can identify strengths and opportunities for improvement related to leadership, vision, values, and strategy, focusing on finance, customers, internal processes, human resources, and performance excellence.